Community Empowerment Through Technological Innovation and Digitalization for the Development of Bamboo Weaving Educational Tourism in Sumuragung Village - Abdul Azis Safii; Marlina Nur Saputri; Latifah Anom; Hasan Bisri; Murtini Murtini (Trescode Green Organization, 2026)
Sumuragung Village has great potential in bamboo weaving crafts that have been passed down through generations, but faces various challenges in business development, such as limited market access, low digital literacy, weak financial management, and a lack of product innovation. This community service program aims to empower bamboo weaving artisans and educational tourism managers through the application of technological innovation and digitalization. The method used includes four stages: socialization to build mutual commitment, training to improve technical and managerial capacity, the application of technology in the form of bamboo slicing tools and an educational tourism website, and mentoring and evaluation to ensure program sustainability. The results of the activities show significant improvements in various aspects, including an increase in production capacity of up to 70%, an increase in artisan income by 65%, the development of 5 new woven product variants (pencil cases, photo frames, and decorative lampshades), and the establishment of a digital marketing system through a website and social media that reaches a wider market. In addition, the formation of professional Pokdarwis (Tourism Awareness Groups) with a clear organizational structure and a transparent financial system is the foundation for the program's sustainability. This program proves that collaboration between academics, village governments, and communities can create sustainable economic transformation based on local wisdom and modern technology.